POTENSI ANTIATEROGENIK KOMBINASI EKSTRAK ETANOL RIMPANG KUNYIT DAN DAUN PEGAGAN DALAM MENURUNKAN RISIKO PENYAKIT KARDIOVASKULAR PADA MODEL HEWAN TIKUS OBES - Kharina Septi Lestari; Aulia Nurfazri Istiqomah; Ai Siti Farihah; Dika Azhar Ramadhan; Marita Kaniawati; Agus Sulaeman (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Obesity is a major risk factor for atherosclerosis and cardiovascular disease, characterized by dyslipidemia and oxidative stress. This study aimed to evaluate the anti-atherogenic effects of a combination of ethanol extracts of turmeric rhizome (Curcuma longa) and gotu kola leaves (Centella asiatica) in obese–hyperlipidemic rats.  Male rats were divided into seven groups: normal, induction, comparator (orlistat 10.8 mg/kgBW), and treatment groups receiving single and combined extracts (ERK, EDP, ERKDP 200:100, ERKDP 100:200 mg/kgBW). Obesity and hyperlipidemia were induced using a high-fat and fructose diet for 60 days. Parameters measured included body weight, lipid profile (TG, HDL, LDL, total cholesterol), Atherogenic Index of Plasma (AIP), and aortic histology. The induction group showed significant increases in body weight, triglycerides, LDL, and AIP (P<0.05). All treatment groups significantly improved lipid profiles and reduced AIP compared to the induction group. The ERKDP 100:200 mg/kgBW combination showed the most optimal effect, with a 51.83% reduction in LDL, a 54.60% decrease in AIP, and a 146% increase in HDL. Histological analysis also demonstrated reduced foam cell formation and improved aortic structure in this group. In conclusion, the combination of turmeric and gotu kola extracts, particularly at a dose of 100:200 mg/kgBW, exhibits significant anti-atherogenic potential through lipid profile improvement, AIP reduction, and vascular protection.